Inclusão da disciplina de gestão em agricultura de precisão no ensino profissionalizante formação técnico em agropecuária - Streck, Carlos Alexandre (2016)
The Precision Agriculture is, within the Agribusiness, one of the drivers of technological development and sustainable production. It is characterized as a set of technologies applied in a farm management system, which allows the results to be the most significant potential in a framework of possibilities where solving strategies of uniformity problems of crops can be addressed. This knowledge of the variability of production and quality, which consists in the use of machinery and equipment, is useful for any culture in small or large scale. The Precision Agriculture is not only about the use of sophisticated machinery and equipment, but also management and administration of the Agricultural Production Unit. With special attention to the need of approximate the knowledge and improvement in precision agriculture, the main objective of this work was offer a new school subject called "Management of Precision Agriculture". The class was offered in the first term of 2016, within the curriculum for the Technical Course in Agriculture in the State Technical School Nossa Senhora da Conceição , Três Vendas district of Cachoeira do Sul RS. The subject, with a workload of 40 hours was planned based on theoretical and practical notions in: Introduction and AP Cycle, Global Navigation Satellite Systems (GNSS), the Aquarius Project History, Precision Agriculture applied in soil science, GIS, Basic Statistics, Agriculture in Machinery and Tools precision, Informatics applied to Precision Agriculture, Information Management, agricultural Equipment Maintenance precision. Evaluation methods of the subject were the application of essay tests, presentation of seminars, preparation of summaries of important topics and also practical classes. As main results, we highlight the good acceptance of the subject for students and people involved in the process, 100% approval of the students and parameters to improve the subject, including the possibility of offering it in the next class.